Exploring the research frontier of life cycle sustainability assessment—a systematic literature review of applied bibliometric analysis - Ma, Sining; Sharaai, Amir Hamzah; He, Zhijian; Matthew, Nitanan Koshy; Zainordin, Nazatul S.; Wafa, Wafaurahman (Italian Association of Chemical Engineering - AIDIC, 2023)
All organizations are impacted by sustainability, both positively and negatively. It is therefore important to assess the sustainability of any human activity, product, or development. Life Cycle Sustainability Assessment (LCSA) is one of the most effective methods for assessing sustainability. The significance of this study is that it highlights significant and key ideas in the subject of LCSA, including research commonality, research trends, model shortcomings, existing appropriate methods, and research gaps using a systematic review of the literature and bibliometric analysis. The developing tendency of reviewing suggests that while sustainability issues are a severe problem for all countries, they will continue to rule social, economic, and environmental issues in the years to come. There are still a lot of uncharted territories. The study found that energy was the most popular topic among related areas of LCSA application. According to the research findings, it was also suggested that LCSA could be improved in future research in the following areas: the development of impact categories to enable study comparison, the definition of coherent system boundaries, the development of impact assessment methodologies, the development of trustworthy databases to enable the evaluation of economic and social perspectives, the development of tools for performing uncertainty analysis and communication strategies. To advance technique development and comprehend the interplay between environmental, economic, and social aspects, more case studies are required. It is envisaged that the development and application of LCSA will contribute to the accomplishment of Sustainable Development Goals across a range of international locations, businesses, and goods.